2000
DOI: 10.1046/j.1460-9568.2000.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids inhibit hippocampal GABAergic transmission and network oscillations

Abstract: Using a new antibody developed against the C-terminus of the cannabinoid receptor (CB1), the immunostaining in the hippocampus revealed additional axon terminals relative to the pattern reported previously with an N-terminus antibody. Due to a greater sensitivity of this antibody, a large proportion of boutons in the dendritic layers displaying symmetrical (GABAergic) synapses were also strongly immunoreactive for CB1 receptors, as were axon terminals of perisomatic inhibitory cells containing cholecystokinin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
388
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(435 citation statements)
references
References 41 publications
34
388
2
4
Order By: Relevance
“…In the hippocampus, CB-1R are located primarily on cholecystokinin containing GABAergic interneurons (Hajos et al, 2000;Katona et al, 2000Katona et al, , 1999aKatona et al, , 1999bTsou et al, 1999). These GABAergic interneurons are believed to orchestrate fast synchronous oscillations in the gamma range, a critical process in synchronizing pyramidal cell activity (Hajos et al, 2000;Hoffman and Lupica, 2000).…”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hippocampus, CB-1R are located primarily on cholecystokinin containing GABAergic interneurons (Hajos et al, 2000;Katona et al, 2000Katona et al, , 1999aKatona et al, , 1999bTsou et al, 1999). These GABAergic interneurons are believed to orchestrate fast synchronous oscillations in the gamma range, a critical process in synchronizing pyramidal cell activity (Hajos et al, 2000;Hoffman and Lupica, 2000).…”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%
“…These GABAergic interneurons are believed to orchestrate fast synchronous oscillations in the gamma range, a critical process in synchronizing pyramidal cell activity (Hajos et al, 2000;Hoffman and Lupica, 2000). Gamma oscillations are synchronized over long distances in the brain and are hypothesized to 'bind' together sensory perceptions and to play a role in cognition (reviewed in Wilson and Nicoll, 2002).…”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%
“…The pattern for hippocampal DSE is further complicated by the uncertainties on the CB receptor isoform mediating the cannabinoid response. In fact, although this is still a disputed issue (Marsicano & Lutz, 1999: Marsicano et al, 2003, some of the presently available evidence suggests that CB1Rs are not present on glutamatergic terminals onto CA1 pyramidal cell (Katona et al, 1999;Tsuo et al, 1999;Hajos et al, 2000), and that a so far uncloned CB receptor might provide the sensitivity to cannabinoids (Hajos et al, 2001;Breivogel et al, 2001). Independently of this issue, the take home message remains that, in the hippocampus, cannabinoidmediated retrograde inhibition appears to pertain mainly to GABAergic synapses .…”
Section: Calcium Dependence Of Dsementioning
confidence: 99%
“…Subsequent work from several labs has extended these studies to central nervous system (CNS) neurons and provides a mechanistic basis for attenuation of neurotransmission by CB1 activation. 5 Presumed mechanisms generally invoke inhibition of presynaptic (eg, N-and P/Q-type) calcium channels 18 , 19 but may also involve activation of potassium channels and CB1-mediated direct inhibition of the vesicular release machinery. 6 …”
Section: Cannabinoids Inhibit Neurotransmissionmentioning
confidence: 99%
“…Indeed, several studies have shown this to be the case. [5][6][7] Given the locations and actions of cannabinoid receptors, one would expect the presence of an endogenous ligand, a prediction that has been borne out. Specifi cally, 2 families of endocannabinoids have been extensively characterized.…”
mentioning
confidence: 99%